Kode Etik Jurnalistik di Kalangan Wartawan Media Massa Cetak Islam - Ilham Prisgunanto (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2017)
The journalistic ethics code seeks to provide freedom and protection to journalists. This study aims to determine the relationship between journalists' understanding of journalistic ethics code with its application from the dimensions of professionalism, dedication, and expertise. The independent variable is the understanding of the journalistic code of ethics and the dependent variables are the professionalism, dedication, and expertise of journalists. The survey research was conducted on 100 journalists working in Islamic mass media in Jakarta. Data analysis used a correlation test. The results show that journalists' understanding of the journalistic code of ethics is high and dedication is the most important dimension in journalist performance in the field. However, the correlation test results indicate a weak relationship between the understanding of the journalistic code of ethics and the professionalism, dedication, and expertise of journalists. This study concludes that journalists have considered the importance of the journalistic ethics in support of their work, but it is lack of implementation.